(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2023)
As part of my undergraduate studies at the School of Arts of the Universidad Central de Venezuela, I had the opportunity to meet and share knowledge with Juan Francisco Sans, who was also the tutor for my degree project, an experience in which he introduced me to critical edition. This essay is an approximation to that fruitful personal encounter with all the imprint it has had on my professional development.